NEW TEACHING STRATEGIES IN THE LEARNING OF THE UNIVERSITY EDUCATION STUDENTS - Colina , Daliangy; Rojas , Elianny (Revista Arbitrada Formación Gerencial, 2024)
This article aims to analyze new teaching strategies to the learning of university education students. The theorical frame was based on the authors Maldonado (2019), Kolb (2015) and Freiberg (2017) The investigation was framed in the qualitative scientific paradigm, using phenomenological method. The informants were four professors of both sexes, with more than four years of experience working in various social, economic and industrial areas. Made the reductions of the method, it emerge the category new teaching strategies in the learning of university education students, emerging two phenomenological categories/synthetized: new teaching strategies and learning styles. The results show the underlying theoretical universal generation.